Fertile Island Effect by Three Typical Woody Plants on Wetlands of Ebinur Lake, northwestern China - Zhang, Yabei; Wang, Hengfang; Cai, Yan; Yang, Qi; Lv, Guanghui (Frontiers in Environmental Science, 2022)
Desertification poses a permanent threat to the security of arid ecosystems. Perennial arid vegetation plays a crucial role in maintaining the structure and function of arid ecosystems and slowing the process of desertification by forming "fertile islands" under the tree canopy. However, the process of formation and development of these fertile islands remains uncertain. Here we explored how three typical woody plants (i.e., Populus euphratica, Haloxylon ammodendron, and Nitraria tangutorum) in the Ebinur Lake Basin of northwestern China differed in their soil nitrogen and phosphorus. (1) There were significant differences of organic carbon, total and available nitrogen/phosphorus in the soil among the three typical woody plants-dominated ecosystems. Populus euphratica had significant differences of N and P contents between the canopy and bare soils, except for ammonium nitrogen. (2) Our RDA analysis revealed that the major factors that influenced the soil nutrient differences among the three vegetations were plant crown width, soil water content, salinity, and pH. (3) The organic carbon content of bare soil was significantly correlated with N and P in all three vegetations. This study contributes to our understanding of the factors that influence the fertilizer island effect in arid ecosystems, which may contribute to soil conservation in arid areas.